Imagination and creativity in music listening - Hargreaves, David; Hargreaves, J.; North, Adrian (Oxford University Press, 2011)
This chapter discusses the notion of imagination and creativity in music listening, viewing perception as creative construction of knowledge. It proposes three networks of cognitive association. The first are networks of musical association: these are the connections that people make between different musical materials, pieces, and styles, and they could be thought of as people's ‘musical geographies’, i.e., the mental maps which they use to interpret any new pieces of the music they might encounter. The second type are networks which are based on the cultural aspects of musical reference, and the concept of ‘musical fit’ is helpful in understanding this: it is simply that certain pieces and styles are seen by members of particular cultural groups as being more appropriate to some situations than to others. Thirdly, it suggests that people construct their own personal networks of association by linking their cultural networks — the key people, situations, and events they have experienced in their lives — with their musical geographies. These may well form the basis of our musical identities.